Effects of dietary supplementation of N‐carbamylglutamate on the haematology parameters, secondary sexual characteristics and testicular gene expression in roosters. Issue 2 (18th April 2022) - Ma, Wei; Dang, De Xin; Zhang, Jiehui; Wang, Chunqiang; Li, Desheng
Abstract: A total of 288 11‐week‐age roosters were used to evaluate the effects of dietary supplementation of N ‐carbamylglutamate (NCG) on reproductive traits and testicular gene expression. The experimental periods were 12 weeks. All birds were randomly assigned to 4 treatments with 6 replicates per treatment and 12 birds per replicate. Dietary conditions were based on a basal diet and supplemented with 0%, 0.08%, 0.12%, or 0.16% NCG to form C, N1, N2 and N3 groups respectively. Dietary supplementation of NCG had positive effects on the seminiferous tubule parameters, serum gonadotropin‐releasing hormone and testosterone levels and the secondary sexual characteristics. Transcriptomics analysis was performed on the testicular tissues between C and N3 groups at the 16‐week‐age. Genes were mainly enriched in nine pathways, such as cytochrome P450 exogenous metabolism, drug metabolism, steroid hormone synthesis and glutathione metabolism, in which the ZP4 gene, cytochrome P450 family member 11A1 and other genes involved in the maintenance of gonadal function, steroid hormone biosynthesis and metabolism, and so forth, exist differences in expression levels. In summary, dietary supplementation of NCG had positive effects on the reproductive traits of roosters. NCG supplementation improved the development of reproductive traits of roosters by regulating the genes expression in testicular tissues and thus improved the synthesis of reproductive hormones in vivo.